STRENGTHENING COOPERATION WITH PAKISTAN - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 9 November 2016 – Groups having different interests in this country are invited to strengthen their cooperation with Pakistan here.